1996
DOI: 10.1006/jare.1996.0124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early season defoliation ofAnthyllis cytisoides(a Mediterranean browse species) on further herbivore attack

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Although the defoliation treatments increased shoot mortality, the surviving shoots were able to keep up total shoot growth through increased lateral shoot growth. Increases in branching and shoot length as a response to leaf removal have been reported in other woody plants (Torres et al 1980;Alados et al 1996). However, such changes may be overridden by later responses to resource loss, as reduced shoot growth may occur 2 years after defoliation (Hjä lté n et al 1993), or after repeated defoliation (Heichel and Turner 1984).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although the defoliation treatments increased shoot mortality, the surviving shoots were able to keep up total shoot growth through increased lateral shoot growth. Increases in branching and shoot length as a response to leaf removal have been reported in other woody plants (Torres et al 1980;Alados et al 1996). However, such changes may be overridden by later responses to resource loss, as reduced shoot growth may occur 2 years after defoliation (Hjä lté n et al 1993), or after repeated defoliation (Heichel and Turner 1984).…”
Section: Discussionmentioning
confidence: 94%
“…Woody species have proved more sensitive to leaf removal at early leaf flush and during reproductive phases than late in the season (Cissé 1980;Teague 1986) and, even though refoliation occurs, high defoliation intensities may cause a reduction in final leaf biomass in the same, or subsequent, growth seasons (Benjamin et al 1995;Bergströ m and Danell 1995;Reichenbacker et al 1996). Refoliated leaves on defoliated branches are usually smaller than mature, initially formed leaves on control branches (Faeth 1992), and several studies have reported a reduction in growth of shoots and height of plants after defoliation (Heichel and Turner 1984;Marquis 1992;Hjä lté n et al 1993;Bergströ m and Danell 1995;Reichenbacker et al 1996), while others have recorded increased branching and total shoot length (Torres et al 1980;Alados et al 1996).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…cytisoides is a perennial leguminous cheamophyte, which grows up to 1Á10 m high and is drought deciduous (Alados, 1996). It has a branching root system with a main taproot that has been measured in open gully walls in the Rambla Honda to grow up to 2Á5 m. It has also been found to grow up to 5 m in softened rock joints or in alluvium (Domingo et al, 1991).…”
Section: Sitementioning
confidence: 97%
“…The 'Anthyllis site', located on an upper alluvial fan, faced north-west and with a slope angle of approximately 8º. The shrub-area was dominated by Anthyllis cytisoides L. (Plate 1), a perennial leguminous drought deciduous cheamophyte up to 1.10 m high (Alados, 1996). It has a branching root system with a main tap root that has been measured in open gully walls in the Rambla Honda to a depth of 2.5 m. The 'Retama site' was on a west facing lower alluvial fan with slopes of 2º in the grass-area and 4º in the shrub-area; this comprised mainly Retama sphaerocarpa L. Boiss (Plate 2), a leguminous shrub with photosynthetic stems, very few leaves and an extensive dual root system; surface roots grow radially from a main stump and very deep vertical roots are capable of abstracting water from depths of 16-20 m (Hasse et al, 1996).…”
Section: Study Sitementioning
confidence: 99%